Karakterisasi Dan Potensi Buangan Akhir Pengolahan Pome Menjadi Air Baku - Dzaki Furqoon; David Andrio; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
POME final discharge is a problem for the palm oil industry at this time because it does not reach the predetermined quality standards and can damage life in aquatic biota. This study aims to determine the characteristics of POME final discharge and to analyze the potential treatment methods for Chemical Oxygen Demand (COD) removal in POME final discharge using the ozonation method. The results showed that the concentrations of COD in POME final discharge were 290.9 mg / L. Duration of contact time in the ozonation method could affect the removal of COD in the POME final discharge. Keywords: POME final discharge, Ozonation